Robotic radical stump trachelectomy: Critical steps of a radical procedure without normal anatomical landmarks - Monica Avila; Jared R. Funston; Mitchel S. Hoffman (Elsevier, 2024)
Background: Cervical stump malignancies are an uncommon finding post subtotal hysterectomy. Tumors arise from a primary cervical origin with an incidence of 1-5%. Other described malignancies can include uterine origin, ovarian origin or as metastases from another primary site. A uterine primary is an extremely rare entity and can result from remnant endometrial tissue at the stump apex. Case: 70yo female with a history of remote supracervical hysterectomy for benign indication who presented with postmenopausal spotting. Endocervical curettage of the endocervical stump revealed a grade 2 endometrioid endometrial adenocarcinoma. She was taken to the operating for a robotic radical stump trachelectomy and sentinel lymph node dissection. Conclusions: The surgical video delineates key surgical steps of robotic radical stump trachelectomy including robotic port placement and injection of ICG dye, adhesiolysis and restoration of normal anatomy, opening of the pelvic spaces and exposure of the retroperitoneum, identification and excision of pelvic sentinel lymph nodes, bladder dissection, ureterolysis and ligation of uterine remnant, ureteric tunnel dissection and mobilization of parametrial wing, delineation of a vaginal margin, colpotomy and specimen removal, and vaginal cuff closure.